Rotator cuff activation during the olympic snatch under various loading conditions - Ernst, A. T.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The current study examined rotator cuff (RTC) muscle activation levels during different phases of the snatch under varied loading conditions, and evaluated shoulder abduction (ABD) angle during the catch. Nine male Olympic weightlifters currently training for competition had surface EMG electrodes attached to their supraspinatus, infraspinatus, and teres minor, then performed two lifts at 40, 60, and 80% of their maximum snatch. 2-D video was used to record each lift and synchronized with the EMG readings to evaluate RTC muscle activation. Markers were placed on the participants` upper extremity to evaluate shoulder ABD angle during these trials. Shoulder ABD angle at the catch did not differ between loading conditions. RTC activation varied throughout the snatch with the supraspinatus and infraspinatus becoming most active during the turnover and catch phases of the lift while the teres minor is most active during the first pull and transition.